2022
DOI: 10.1371/journal.pntd.0010422
|View full text |Cite
|
Sign up to set email alerts
|

Oral rabies vaccination of dogs—Experiences from a field trial in Namibia

Abstract: Dog-mediated rabies is responsible for tens of thousands of human deaths annually, and in resource-constrained settings, vaccinating dogs to control the disease at source remains challenging. Currently, rabies elimination efforts rely on mass dog vaccination by the parenteral route. To increase the herd immunity, free-roaming and stray dogs need to be specifically addressed in the vaccination campaigns, with oral rabies vaccination (ORV) of dogs being a possible solution. Using a third-generation vaccine and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Hence, both vaccine container and bait were replaced by an egg-flavoured bait containing a soft blister. Bait acceptance studies showed that the egg-flavoured bait with soft blister was not only very attractive to the dogs but was also capable of timely release of the vaccine in the oral cavity during bait consumption [ 28 , 29 , 63 ]. These results were corroborated by this efficacy study, where all animals accepted and ingested the egg-flavoured bait readily and, subsequently, perforated the soft blister.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, both vaccine container and bait were replaced by an egg-flavoured bait containing a soft blister. Bait acceptance studies showed that the egg-flavoured bait with soft blister was not only very attractive to the dogs but was also capable of timely release of the vaccine in the oral cavity during bait consumption [ 28 , 29 , 63 ]. These results were corroborated by this efficacy study, where all animals accepted and ingested the egg-flavoured bait readily and, subsequently, perforated the soft blister.…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine is registered in the European Union (EU) since December 2017 and used for the ORV of foxes and raccoon dogs in several EU member states [ 25 ]. It has also been intensively studied for the ORV of free-roaming dogs during experimental and field studies in different countries [ 26 , 27 , 28 , 29 , 30 ]. With the successful completion of the efficacy study presented here, this vaccine virus meets all required safety and efficacy standards, thus, hopefully eliminating the last hurdle for the integration of the ORV of dogs in areas with high proportions of dogs that are inaccessible for parenteral vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of clearly defined administrative boundaries for villages/settlements and an official HH register for NCAs, so-called "crush pens" (n = 194) were used as a starting point for selecting HHs to be interviewed and randomly selected using available GIS layers. Crush pens are uniformly distributed, permanent facilities within NCAs that are regularly used as vaccination sites for cattle but also for targeted mass vaccination campaigns for dogs [ 8 , 10 , 44 ]. To achieve the sample size, survey teams were required to interview at least 15 HH in the vicinity of selected crush pens.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of clearly defined administrative boundaries for villages/settlements and an official HH register for NCAs, so-called “crush pens” (n=194) were used as a starting point for selecting HHs to be interviewed and randomly selected using available GIS layers. Crush pens are uniformly distributed, permanent facilities within NCAs that are regularly used as vaccination sites for cattle but also for targeted mass vaccination campaigns for dogs [8,10,43]. To achieve the sample size, survey teams were required to interview at least 15 HH in the vicinity of selected crush pens.…”
Section: Methodsmentioning
confidence: 99%
“…Survey data were collected via mobile phones using the Worldwide Veterinary Service smartphone App (WVS Data collection App) essentially as described (Gibson et al, 2018, Freuling et al, 2022. The App and its template were kindly provided by the nongovernmental organization Mission Rabies (https://missionrabies.com/).…”
Section: Data Collectionmentioning
confidence: 99%